Effectiveness of the Hunter Way Back Support Service: An historical controlled trial of a brief non‐clinical after‐care program for hospital‐treated deliberate self‐poisoning. Issue 3 (5th February 2022) - McGill, Katie; Whyte, Ian M.; Sawyer, Lisa; Adams, Danielle; Delamothe, Katrina; Lewin, Terry J.; Robinson, Jo; Kay‐Lambkin, Frances J.; Carter, Gregory L.
Abstract: Introduction: Active contact and follow‐up interventions have been shown to be effective in reducing repetition of hospital‐treated self‐harm. The Way Back Support Service (WBSS) is a new service funded by the Australian government to provide three months of non‐clinical after‐care following a hospital‐treated suicide attempt. The aim of this study was to investigate the effectiveness of WBSS in reducing deliberate self‐poisoning (DSP) and psychiatric hospital admissions over a 12‐month follow‐up period for a population of DSP patients within the Hunter (Australia) region. Methods: A non‐randomized, historical controlled (two periods) trial design with intention‐to‐treat analyses. Outcome data were drawn from hospital records. Results: There were a total of 2770 participants across study periods. There were no significant differences between cohorts for proportion with any, or number of, re‐admissions for DSP in the follow‐up period. For psychiatric admissions, the intervention cohort had a non‐significantly greater proportion with any psychiatric admission and significantly more admissions compared to one of the control cohorts. Conclusion: The WBSS model of care should be modified to strengthen treatment engagement and retention and to include established, clinical, evidence‐based treatments shown to reduce DSP repetition. Any modified WBSS model should be subject to further evaluation.